THE ANALYSIS OF CREDIT FINANCING OF HOME OWNERSHIP WITH MURABAHAH AT PT. BANK SYARIAH MANDIRI PALEMBANG - Muhammad Fahmi; Poppy Febrina (Faculty of Economics and Business, Hasanuddin University, 2019)
The purpose of this study was to find out whether the housing loan financing (mortgage) at Bank Syariah Mandiri Palembang Branch in accordance with murabaha and to know the process of granting mortgage with murabahah scheme in Bank Syariah Mandiri Branch Palembang to prospective recipients of financing. The research method used was descriptive method that was by collecting the data obtained and then interpret and analyze so as to provide information that can be used to solve the problems encountered. The data used were primary data and secondary data. The results of this study indicate mortgage loans at PT. Bank Syariah Mandiri has been in accordance with the murabahah financing agreement and analysis on PSAK No. 102 concerning Murabahah as the basis of consideration of the Conformity of House Ownership Credit at Bank Syariah Mandiri Palembang Branch Office.